Pax2-Islet1 Transgenic Mice Are Hyperactive and Have Altered Cerebellar Foliation - Bohuslavova, Romana; Dodd, Nicole; Macova, Iva; Chumak, Tetyana; Horak, Martin; Syka, Josef; Fritzsch, Bernd; Pavlinkova, Gabriela (Molecular neurobiology, 2017)
The programming of cell fate by transcription factors requires precise regulation of their time and level of expression. The LIM-homeodomain transcription factor Islet1 (Isl1) is involved in cell-fate specification of motor neurons, and it may play a similar role in the inner ear. In order to study its role in the regulation of vestibulo-motor development, we investigated a transgenic mouse expressing Isl1 under the Pax2 promoter control (Tg +/- ). The transgenic mice show altered level, time, and place of expression of Isl1 but are viable. However, Tg +/- mice exhibit hyperactivity, including circling behavior, and progressive age-related decline in hearing, which has been reported previously. Here, we describe the molecular and morphological changes in the cerebellum and vestibular system that may cause the hyperactivity of Tg +/- mice. The transgene altered the formation of folia in the cerebellum, the distribution of calretinin labeled unipolar brush cells, and reduced the size of the cerebellum, inferior colliculus, and saccule. Age-related progressive reduction of calbindin expression was detected in Purkinje cells in the transgenic cerebella. The hyperactivity of Tg +/- mice is reduced upon the administration of picrotoxin, a non-competitive channel blocker for the γ-aminobutyric acid (GABA) receptor chloride channels. This suggests that the overexpression of Isl1 significantly affects the functions of GABAergic neurons. We demonstrate that the overexpression of Isl1 affects the development and function of the cerebello-vestibular system, resulting in hyperactivity.
Keywords: Vestibule, Labyrinth; Male; mozeček; transkripční faktor PAX2; Animals; vestibulární aparát; GABA signaling; Mice, Transgenic; Mice; Islet1 transcription factor; Transcription Factors; mužské pohlaví; Female; Cerebellum; Hyperkinesis; Vestibular system; LIM-Homeodomain Proteins; Purkinje cells; hyperkineze; Attention deficit hyperactivity disorder; ženské pohlaví; myši transgenní; zvířata; Calcium homeostasis; Transgenic mouse; Foliation defects; proteiny s homeodoménou LIM; transkripční faktory; Hyperactivity; Age-related deterioration of Purkinje cells; PAX2 Transcription Factor; myši